How are socioeconomic status, social support, and health history associated with unhealthy lifestyle behaviours in middle-aged adults? Results of the Swedish CArdioPulmonary bioImage Study (SCAPIS) COHORT - Leonie Klompstra; Marie Löf; Cecilia Björkelund; Mai-Lis Hellenius; Lena V. Kallings; Marju Orho-Melander; Patrik Wennberg; Preben Bendtsen; Marcus Bendtsen (Archives of Public Health)
Abstract Background Unhealthy lifestyle behaviours, including unhealthy alcohol consumption, physical inactivity, smoking, and nonadherence to dietary recommendations, are major contributors to non-communicable diseases and mortality. While adopting healthy behaviours can reduce these risks in middle-aged adults, research is limited. Therefore, the aim of this study was to assess the distribution of unhealthy lifestyle behaviours in middle-aged adults and their associations with socioeconomic factors, social support, and history of disease. Method This was a cross-sectional study of the Swedish CArdioPulmonary bioImage Study (SCAPIS) cohort (2013–2018) at six Swedish university hospitals. Multilevel regression models were estimated using Bayesian inference with priors shrinking covariate estimates towards the null. Results In total, 59 909 participants, aged 50–64 years old were invited to SCAPIS, of which 30 154 (50.3%) decided to participate. The mean age of participants was 58 (SD = 4) years old, and 51% were women (n = 15 508). Men had higher unhealthy alcohol consumption and were less adherent to dietary recommendations compared to women. Older participants were more physically inactive compared to younger participants. Low education and financial difficulties were associated with smoking, physical inactivity, and poor diet adherence. Financial difficulties were also associated with unhealthy alcohol consumption. Having more people to turn to in difficulties was associated with lower alcohol consumption. Lack of appreciation and comfort support was associated with smoking and poor diet adherence. Diabetes was associated with lower alcohol consumption. Diabetes and lung diseases were associated with smoking and inactivity. Conclusions Middle-aged adults with lower socioeconomic status, less quality social support, and a history of disease were more likely to engage in unhealthy behaviours. This study helps to identify groups of middle-aged adults who may require additional attention when it comes to prioritizing the development of preventive measures.